2019
DOI: 10.5194/acp-19-1971-2019
|View full text |Cite
|
Sign up to set email alerts
|

A proxy for atmospheric daytime gaseous sulfuric acid concentration in urban Beijing

Abstract: Abstract. Gaseous sulfuric acid (H2SO4) is known as one of the key precursors for atmospheric new particle formation (NPF) processes, but its measurement remains challenging. Therefore, a proxy method that is able to derive gaseous sulfuric acid concentrations from parameters that can be measured relatively easily and accurately is highly desirable for the atmospheric chemistry community. Although such methods are available for clean atmospheric environments, a proxy that works well in a polluted atmosphere, s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 76 publications
3
47
0
Order By: Relevance
“…High concentrations of SO 2 have been ascribed to regional pollution and an anthropogenic condensation sink even in semipristine environments (Dada et al, 2017). Earlier observations report that the main sources of SO 2 are power plants, traffic and industry, so SO 2 can be used as a tracer for regional pollution Lu et al, 2010). Generally, as shown in Fig.…”
Section: Connection With Somentioning
confidence: 99%
“…High concentrations of SO 2 have been ascribed to regional pollution and an anthropogenic condensation sink even in semipristine environments (Dada et al, 2017). Earlier observations report that the main sources of SO 2 are power plants, traffic and industry, so SO 2 can be used as a tracer for regional pollution Lu et al, 2010). Generally, as shown in Fig.…”
Section: Connection With Somentioning
confidence: 99%
“…Sulfuric acid (H 2 SO 4 ), which has a very low saturation vapor pressure and strong hydrogen bonding capability (Zhang et al, 2011), has been found to be the major precursor of atmospheric NPF (Weber et al, 1996;Kulmala et al, 2004;Sihto et al, 2006;Sipilä et al, 2010;Erupe et al, 2011;Lehtipalo et al, 2018;Ma et al, 2019) and is often used in global models for simulating the occurrence and intensity of new particle formation events (Dunne et al, 2016). However, atmospheric measurements of gas-phase sulfuric acid are rare, mainly due to its low concentration (10 6 -10 7 molecules cm −3 or below) that can only be measured using state-of-the-art instruments (Mikkonen et al, 2011), such as the chemical ionization atmospheric-pressure interface time-of-flight spectrometer (CI-APi-ToF) (Eisele and Tanner, 1993;Jokinen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Class III can be further classified into three growth patterns, which will be detailed in later sections. In addition to particle size, various factors such as chemical composition, particle mixing states, and meteorological conditions may also largely affect CCN activation of aerosols with D pg beyond 70 nm (Ma et al, 2016;Rose et al, 2017;Lee et al, 2019). Although new particles in class III can grow to CCN size, the CCN activation of grown new particles has been reported to vary case by case (Wiedensohler et al, 2009;Yue et al, 2011;Li et al, 2015;Ma et al, 2016).…”
Section: Season-dependent Growth Patterns Of Newly Formed Particlesmentioning
confidence: 99%
“…Modeling studies have also proposed that approximately 50 % of the CCN population is attributable to NPF events in the troposphere (Yu and Luo, 2009;Yu et al, 2014;Gordon et al, 2017). Nevertheless, reported observations have also shown that newly formed particles with diameters less than 40-50 nm can be activated as CCN only under high supersaturation (SS), such as > 0.6 % (Li et al, 2015;Ma et al, 2016). When newly formed particles grow to a geometric median diameter of larger than 70 nm, they significantly contribute to the CCN population at SS ≤ 0.2 % (Wiedensohler et al, 2009;Yue et al, 2011;Li et al, 2015;Ma et al, 2016;Zhu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation